Internet of things challenges, advances, and applications - Hassan, Qusay F.; Khan, Atta ur Rehman; Madani, Sajjad A. (Chapman & Hall/CRC Computer and Information Science Series, 2018)
This book provides a comprehensive introduction to IoT, related technologies, and common issues in the adoption of IoT on a large scale. The book is an excellent reference for researchers and post-graduate students working in the area of IoT, or related areas. It also targets IT professionals interested in gaining deeper knowledge of IoT, its challenges, and application areas.